Traditional Banjar Cuisine as a Cultural Innovation for Numeracy Learning in Early Childhood Education - Koenarso, Dyah Ageng Pramesty; Azzahra, Muzahadah; Fauziah, Annisa (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2025)
Early numeracy learning in Indonesian early childhood education often lacks cultural and daily life connections. This study explores how wadai lempeng pisang (Banjar-style banana pancake) can be used as a culturally responsive medium for numeracy development. A qualitative descriptive approach was applied through classroom observation, teacher and parent interviews, and documentation in a kindergarten in South Kalimantan. Data were analyzed using Miles, Huberman, and Saldaña’s interactive model with triangulation for validity. Findings show that the cooking activity naturally fostered counting, measuring, sequencing, comparing, and problem-solving. For example, children counted bananas, measured sugar with spoons, sequenced cooking steps, and adjusted dough consistency—developing both symbolic and practical mathematical skills. This activity also enhanced engagement, inclusivity, and cultural identity, as children related the experience to their home practices. The study concludes that integrating local culinary traditions into numeracy learning provides meaningful, hands-on experiences that support both cognitive and affective development. It offers an adaptive pedagogical model for early childhood education, especially in culturally rich regions.